Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Group Investigasion di SD - Petriza, Narila; Eliyasni, Rifda (Universitas Negeri Padang, 2022)
The purpose of this study was to improve students' integrated thematic learning outcomes by using the cooperative group investigation type model. Integrated thematic learning is learning that uses themes as the main focus. This learning provides meaningful experiences to students because in integrated thematic learning students will understand the concepts they learn through direct and real experiences. This research method, using classroom action research methods. The research procedure is in the form of a cycle. Each cycle consists of four stages including: planning, implementing actions, observing, and reflecting. Data collecting techniques through observation and tests. This data collection uses an instrument in the form of student and teacher observation observation sheets in the learning process, while to determine the quality of student learning outcomes, evaluation / test sheets are used. The results showed that the use of the investigational group type cooperative model could improve students' integrated thematic learning outcomes. From the average value in the first cycle, 73.80% to 90.97% in the second cycle.